The Broadcast Pulic and Its Problems - Nyre, Lars (Javnost-The Public, 2011)
It was a loss for Western democracies that wireless transmission technologies, which were discovered and invented from around 1900, became broadcasting and not something more democratic. Transmission acquired a centralised structure, an expert-oriented journalistic ethics, and a relatively passive domestic culture of reception. This was good, but not good enough. In strictly technical terms, the new transmission technologies could have been constructed as a participatory public platform. Transmission could have become an everyday realisation of John Dewey’s democratic vision, but it ended up as one-way media in the spirit of Walter Lippmann. Much has happened in radio and television since then; there has been a slow and determined increase in audience activity and user-generated content from the 1990s, and television has been rejuvenated with reality TV and talent shows, and other things. However, transmission still does not support participatory communication to the extent that it could technically have done. This article critiques the Western broadcast media industry and its scholars for being too complacent about radical change in a participatory direction. By appealing to the political energies of the “Lippmann-Dewey debate,” the article pits the dominant paradigm of broadcasting against a participatory communication ethics that has not yet had a chance to prove itself technologically and socially. It deals with three interrelated problems of the broadcast public: (1) an elitist rationale for the construction of a oneway technological infrastructure, (2) a lack of social equality between professionals and amateurs, and (3) a commercial rhetoric of the media empowered citizen. If these three problems were solved or at least countered more robustly by a participatory communication ethics, the live transmission of sounds and images might fi nally realise their public potential.